Improving early exclusion of acute coronary syndrome in primary care: the added value of point-of-care troponin as stated by general practitioners. Issue 4 (2nd May 2017) - Kip, Michelle M.A.; Noltes, Amber M.; Koffijberg, Hendrik; IJzerman, Maarten J.; Kusters, Ron
Abstract : Aim: To investigate general practitioners' (GPs') desire and perceived added value of point-of-care (POC) troponin, its effect on referral decisions, and test requirements. Background: Excluding acute coronary syndrome (ACS) in primary care remains a diagnostic challenges for GPs. Consequently, referral rates of chest pain patients are high, while the incidence of a cardiovascular problem is only 8–15%. Previous studies have shown that GPs are interested in a POC troponin test. This test could enhance rapid exclusion of ACS, thereby preventing unnecessary patient distress, without compromising safety and while reducing costs. However, using this test is not recommended in current guidelines due to uncertainty in the test's potential added value, and the lower sensitivity early after symptom onset as compared with troponin tests in a regular laboratory. Methods: An online survey containing 34 questions was distributed among 837 Dutch GPs in June 2015. Findings: A total of 126 GPs (15.1%) completed at least 75% of the questions. 67.1% of GPs believe that POC troponin tests have moderate to very high added value. Although the availability of a POC test is expected to increase the frequency at which troponin tests are used, it likely decreases (immediate) referral rates. Of the responding GPs, 78.3% only accept 10 min as the maximum test duration, 78.1% think reimbursement of the POC device is required for implementation, and 68.9% consider it necessary that it can be performed with a finger prick blood sample. In conclusion, according to GPs, the POC troponin test can be of added value to exclude ACS early on. Actual test implementation will depend on test characteristics, including test duration, type of blood sample required, and reimbursement of the analyzer.